MAŁŻEŃSTWO JAKO WARTOŚĆ W OKRESIE PRZEMIAN SPOŁECZNO-GOSPODARCZYCH KRAJU W ŚWIETLE POSTAW MŁODZIEŻY W WIEKU MATRYMONIALNYM W WOJEWÓDZTWIE POZNAŃSKIM - Ignatczyk, Walentyna (Wydział Prawa i Administracji UAM, 2000)
Changes that occurred in Poland recently have liberated some factors that became the reason for to come out of such a kind of behaviour which is contradictory with traditional system of values accepted in this society for many years now. Assuming that the youth is the most pliable for all kinds of influences an attempt has been undertaken to identify the system of values of young people. The article presents results of a research work made in the region of Poznań (in 1995/96) that concerned such issues as: choice to be made - professional career of family life, relation with institutional form of marriage, desired age for marrying, pre-conditions of marrying and identification of the existing hierarchy of marital values. The research made has confirmed that Polish youth is still manifesting attitudes that do accept institutional form of marriage. This youth prefers to choose family life rather than professional career but, in the same time, its liberal attitude to institutional behaviour patterns that are strange to Polish culture and tradition - is also being manifested. Among various conditions of a decision to marry - three following aspects are predominating: emotional, material and that relating to housing standard. Bothering manifestation which could influence marital and procreational behaviour of the youth are the opinions of young people that difficult living conditions involved with difficult, presently at least, social and economic position of the country - can become a cause for such a behaviour that is in disagreement with the attitudes confessed.
MARRIAGE AS A MORAL VALUE IN THE PERIOD OF SOCIAL AND ECONOMIC TRANSFORMATIONS OF THE COUNTRY IN THE LIGHT OF ATTITUDES OF THE YOUTH OF MARITAL AGE IN THE VOIVODSHIP OF POZNAŃ